THE REASONS OF PRIME MINISTER DAVID CAMERON HOLDING REFERENDUM ON THE UNITED KINGDOM’S MEMBERSHIP IN EUROPEAN UNION Compiled and - Tiesya Novia Nur Perdana (HI 16 UMY 161, 2016)
*161 In 22 January 2013, The Prime Minister was promised that he will give in/out referendum about the United Kingdom membership in European Union if his Conservative party win the election in 2015. At the first time, the Prime Minister David Cameron was still considering to do renegotiation with the European Union about the reform that become the UK’s desire. But until David Cameron was re-elected as the Prime Minister of the United Kingdom in May 2015, the renegotiation between the UK and the European Union although the European Union promised that they will change some policies if the remain in EU, it was still found the deadlock. This difficult condition has brought the Prime Minister David Cameron announced that the referendum will be held in 23 June 2016. This date is earlier than the plan before which mentioned that the referendum will be held in the end of 2017. This aims of this research is intended to more investigate about the actors behind the referendum as the foreign decision that took by the Prime Minsiter David Cameron to fulfill the desire of the British people who want the reform inside of European Union’s policies. This research is based on the main sources and information which collected from the first period of the Prime Minister David Cameron in 2010 until the second period of the Prime Minister David Cameron administration in 2016. This research use the Bureaucratic/Governmental model that come from the foreign policy making process by Graham T. Allison. Based on the Bureaucratic/Governmental model by Graham T. Allison it is explained that before the final decision maker decide the foreign policy, there is a bargaining process within the government. The input first come from certain factors such as issue/deals, media, entities, and election then by certain actors, they try to do bargaining process with the final decision maker and finally it is come out as the output or foreign policy. It is concluded that the actors such as eurosceptics actor (mainly eurosceptic governments), business leader actors, and media actors become the main reasons of Prime Minister David Cameron holding referendum which will be held at 23 June, 2016.